The Development of Indonesian Press Freedom in the Period of Old Order (1950-1965) - Sebastian, Andi; Yuwono, Ardi Tri; Clumpers, Pieter-Jan; Basara, Mustafa (Kalijaga Journal of Communication, 2025)
Freedom of the press is a basic principle that affirms that communication and expression through various channels, including publications, must be seen as a right that can be exercised without restrictions. However, during the Old Order period (1950-1965), the condition of the press in Indonesia fluctuated. This research aims to explore more deeply about press freedom in the Old Order era. The method used in this study is a historical method with a qualitative approach. In 1950-1956, the Indonesian press enjoyed a significant degree of freedom, where they could criticize the government through the print media. However, starting in 1956, signs of a decline in press freedom began to be seen, caused by the Old Order government's discomfort with criticism made by the press. In 1958, the government began to control the press by requiring a Printing Permit. When President Soekarno consolidated his power and began the era of guided democracy (1959-1965), press freedom in Indonesia effectively ended. This resulted in the press being under the control of Sukarno's power, although the press succeeded in overthrowing the power after the G30S incident in 1965.